2009
DOI: 10.1111/j.1533-2500.2008.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Neurolysis of the Sciatic and Femoral Nerves to Improve Pressure Ulcer Healing

Abstract: We present our experience with a paraplegic man who suffered from chronic right trochanteric and ischial pressure ulcers that failed to heal despite surgical and conservative treatment. We report the successful treatment of knee and hip flexor spasticity with a femoral and sciatic alcohol neuroablation technique. It was not until the successful control of his lower extremity spasticity that the pressure ulcers showed signs of healing. Neuroablation nay be considered for spasticity control when more conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(20 reference statements)
0
7
0
1
Order By: Relevance
“…Chemodenervation in spinal cord injury J Lui et al individuals with SCI have been reported in four level 4 pre-post studies [35][36][37][38] and six level 5 studies (5 case series/studies, [40][41][42][43][44] one retrospective chart review 39 ). Results from these studies are summarized in Table 3.…”
Section: Levels Of Evidence Bontmentioning
confidence: 99%
See 4 more Smart Citations
“…Chemodenervation in spinal cord injury J Lui et al individuals with SCI have been reported in four level 4 pre-post studies [35][36][37][38] and six level 5 studies (5 case series/studies, [40][41][42][43][44] one retrospective chart review 39 ). Results from these studies are summarized in Table 3.…”
Section: Levels Of Evidence Bontmentioning
confidence: 99%
“…Ghai et al, 35 Yasar et al 39 and Uchikawa et al 37 used MAS as a primary outcome measure, otherwise selection of outcome measures was variable between studies. The three case studies [42][43][44] did not report formal outcome measures and instead provided qualitative descriptions.…”
Section: Levels Of Evidence Bontmentioning
confidence: 99%
See 3 more Smart Citations